Understanding sheath blight resistance in rice: the road behind and the road ahead. Issue 4 (29th January 2020) - Molla, Kutubuddin A.; Karmakar, Subhasis; Molla, Johiruddin; Bajaj, Prasad; Varshney, Rajeev K.; Datta, Swapan K.; Datta, Karabi
Summary: Rice sheath blight disease, caused by the basidiomycetous necrotroph Rhizoctonia solani, became one of the major threats to the rice cultivation worldwide, especially after the adoption of high‐yielding varieties. The pathogen is challenging to manage because of its extensively broad host range and high genetic variability and also due to the inability to find any satisfactory level of natural resistance from the available rice germplasm. It is high time to find remedies to combat the pathogen for reducing rice yield losses and subsequently to minimize the threat to global food security. The development of genetic resistance is one of the alternative means to avoid the use of hazardous chemical fungicides. This review mainly focuses on the effort of better understanding the host–pathogen relationship, finding the gene loci/markers imparting resistance response and modifying the host genome through transgenic development. The latest development and trend in the R. solani –rice pathosystem research with gap analysis are provided.